SOCIAL CONSOLIDATION AND EDUCATION (Pedagogy of Higher and Secondary Education, 2004)
The article deals with certain educational problems of nowadays European community: the mice of the illiterate, theexpulsion of pupils from schools, inadequate level graduates. Special attention is given to minimal standards and different levels of command in education.
Keywords: 1